Social and psychological aspects and models of advertising - Giorgi Abazadze (Theoretical Hypotheses and Empirical Results, 2024)
The impact of advertising on consumers has been studied in detail and exhaustively by a number of researchers who study the psychological aspects of advertising. The psychological aspect of advertising includes basic functions, its influence and impact on psychological mechanisms, basic psychological models of advertising and consumer behavior. In the short term, advertising helps to increase awareness and trust in the company, and in the long term, it helps to build product/brand attachment and a positive reputation.